Efficacy and Safety of Postvitrectomy Intravitreal Triamcinolone Therapy for Diabetic Macular Edema. Issue 5 (September 2016) - Costa, José F.; Sousa, Keissy; Marques, João P.; Marques, Marco; Cachulo, Maria Luz; Silva, Rufino; Gomes, Nuno; Figueira, João
Purpose: After vitrectomy, diffusion and clearance rates of numerous drugs are increased, leading to a shorter intravitreal half-life. This raises doubts about the efficacy of intravitreal therapies, as retina specialists generally believe that a shorter half-life compromises the drugs' therapeutic effect. We conducted a study to evaluate the functional and anatomical effect of intravitreal triamcinolone acetonide therapy (IVTA) in previously vitrectomized eyes with diabetic macular edema (DME). Methods: In this retrospective, multicenter case series study including vitrectomized patients with DME who underwent IVTA injections, central macular thickness (CMT) measured with spectral-domain optical coherence tomography and best-corrected visual acuity (BCVA) in Early Treatment Diabetic Retinopathy Study letters were evaluated after each procedure. All relevant medical data were collected, including previous ophthalmologic treatments and comorbidities. Results: Twenty vitrectomized eyes of 20 patients, mean age 58.1 years (range 40-72 years), were enrolled in the study. All patients presented DME and received at least one IVTA injection. Mean time between pars plana vitrectomy and IVTA was 12.9 ± 8.7 months. Mean pretreatment and posttreatment CMT was 438.8 ± 90.8 μm and 301.2 ± 76.2 μm, respectively, a difference that reached statistical significance (p<0.001). Mean gain in BCVA letter score was 7.83 ± 14.9 letters after treatment (p = 0.039). Mean intraocular pressure was significantly increased after IVTA (17.2 ± 1.9 mm Hg at baseline vs 21.2 ± 4.59 mm Hg after IVTA, p = 0.002). Conclusions: A positive anatomical and functional effect was observed in our cohort. Our results suggest that, despite prior vitrectomy, triamcinolone remains a valid therapeutic approach for eyes with persistent DME. Further prospective randomized studies with larger patient samples are needed to validate this conclusion.